2015
DOI: 10.5901/mjss.2015.v6n4s3p612
|View full text |Cite
|
Sign up to set email alerts
|

Personality and Clinical Dimensions of Pathological Gamblers. A Pilot Study

Abstract: Gambling disorder is characterized by a persistent

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Several correspondences regarding neurobiological evidence, comorbidity, symptomatic behaviour, susceptibility to treatment and aspects of the course, motivated the DSM-5 task force to move GD in the section of addiction disorders (Hasin et al, 2013), confirming that the addictive propensity may develop both from substances and from behaviours (Caretti et al, 2018;Perales et al, 2020). In this regard, several studies showed that gambling behaviours may represent an external regulator of internal emotional states (Di Trani et al, 2017;Gori et al, 2016;Pace et al, 2015;Rogier & Velotti, 2018) and it correlated significantly with traumatic experiences (Hodgins et al, 2010;Lane et al, 2016), insecure attachment (Sherrer et al, 2007) and psychopathological traits, such as alexithymia (Bibby, 2016;Gori et al, 2016;Iraci-Sareri & Gori, 2012;Maniaci et al, 2015) and dissociation (Craparo et al, 2015;Gori et al, 2016;Griffiths et al, 2006;Schluter & Hodgins, 2019;Williams et al, 2012). On the other hand, other researchers suggested the presence of high levels of impulsiveness, compulsiveness and obsessiveness in pathological gamblers (El-Guebaly et al, 2012;Chowdhury et al, 2017;Okechukwu, 2019;Steel & Blaszczynski, 2002), supporting the views which consider craving as a construct of central importance in the maintenance and exacerbation of gambling disorder (Blaszczynski & Nower, 2002;Brevers & Noël, 2013;Sharpe, 2002), but also in the difficulty of treatment and the tendency to relapse (Oei & Gordon, 2008;Smith et al, 2010).…”
Section: Introductionmentioning
confidence: 93%
“…Several correspondences regarding neurobiological evidence, comorbidity, symptomatic behaviour, susceptibility to treatment and aspects of the course, motivated the DSM-5 task force to move GD in the section of addiction disorders (Hasin et al, 2013), confirming that the addictive propensity may develop both from substances and from behaviours (Caretti et al, 2018;Perales et al, 2020). In this regard, several studies showed that gambling behaviours may represent an external regulator of internal emotional states (Di Trani et al, 2017;Gori et al, 2016;Pace et al, 2015;Rogier & Velotti, 2018) and it correlated significantly with traumatic experiences (Hodgins et al, 2010;Lane et al, 2016), insecure attachment (Sherrer et al, 2007) and psychopathological traits, such as alexithymia (Bibby, 2016;Gori et al, 2016;Iraci-Sareri & Gori, 2012;Maniaci et al, 2015) and dissociation (Craparo et al, 2015;Gori et al, 2016;Griffiths et al, 2006;Schluter & Hodgins, 2019;Williams et al, 2012). On the other hand, other researchers suggested the presence of high levels of impulsiveness, compulsiveness and obsessiveness in pathological gamblers (El-Guebaly et al, 2012;Chowdhury et al, 2017;Okechukwu, 2019;Steel & Blaszczynski, 2002), supporting the views which consider craving as a construct of central importance in the maintenance and exacerbation of gambling disorder (Blaszczynski & Nower, 2002;Brevers & Noël, 2013;Sharpe, 2002), but also in the difficulty of treatment and the tendency to relapse (Oei & Gordon, 2008;Smith et al, 2010).…”
Section: Introductionmentioning
confidence: 93%
“…The total number of participants included in our study is 3,210 (varying from a minimum of 17 to a maximum of 996), with a prevalence of male subjects (1,924—gender was the missing data from Craparo et al, 2015; Kofoed et al, 19978). The samples’ natures differed across studies.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the heterogeneity of the measures used, the link between gambling behavior and dissociation was supported by almost all studies (Cartmill et al, 2015; Craparo et al, 2015; Dixon et al, 2019; Kofoed et al, 1997; Kuley & Jacobs, 1988; Murch & Clark, 2019; Murch et al, 2017). DGs seemed more likely to experience several dissociative-like states, as compared to community samples (Diskin & Hodgins, 1999; McCormick et al, 2012).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations